PENGARUH KOMITMEN ORGANISASIONAL DAN PROFESIONAL TERHADAP KEPUASAN KERJA AUDITOR DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Kantor Akuntan Publik di Semarang) - Rahadyan Probo Tranggono; Andi Kartika (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2008)
Job satisfaction is very necessary for any profession. Job satisfaction of auditorincreasingly paid attention to increase performance so that purpose of reachable company ororganization. Many factors which can increase job/activity one of them is commitment.Commitment of it self divided to become two types, those are organizational commitment andprofessional commitment. How far commitment influence to job satisfaction is tested to returns toin this research, by peeping out motivation is intervening variables.Test utilized to analyze commitment influence to job satisfaction that is regression test,path analysis as well as statistic T test. Research data obtained from questionary answerpropagated to the auditors working for Kantor Akuntan Publik in Semarang. Result of researchanalysis express that commitment has positive influence and significant to job satisfaction ofAuditor. From knowable path analysis that relation between organizational commitment and alsoprofessional commitment is relationship that is direct without. Existence of motivation asintervening variable. So it job satisfaction of auditor wish to be improved, hence an auditors shallhave high commitment either that is to the organization and also profession.Key words: organizational commitment, professional commitment, motivation and jobsatisfaction.